An efficient metal-free and catalyst-free C–S/C–O bond-formation strategy: synthesis of pyrazole-conjugated thioamides and amides - Sharma, Shubham; Singh, Dharmender; Kumar, Sunit; Vaishali; Jamra, Rahul; Banyal, Naveen; Deepika; Malakar, Chandi C.; Singh, Virender (Beilstein Journal of Organic Chemistry, 2023)
An operationally simple and metal-free approach is described for the synthesis of pyrazole-tethered thioamide and amide conjugates. The thioamides were generated by employing a three-component reaction of diverse pyrazole C-3/4/5 carbaldehydes, secondary amines, and elemental sulfur in a single synthetic operation. The advantages of this developed protocol refer to the broad substrate scope, metal-free and easy to perform reaction conditions. Moreover, the pyrazole C-3/5-linked amide conjugates were also synthesized via an oxidative amination of pyrazole carbaldehydes and 2-aminopyridines using hydrogen peroxide as an oxidant.
Keywords: C–S/O bond formation; metal-free; oxidative amidation; pyrazole carbaldehydes; sulfur insertion; thioamides

(untitled) - Da Costa, L.; Scheers, E.; Coluccia, A.; Casulli, A.; Roche, M.; Di Giorgio, C.; Neyts, J.; Terme, T.; Cirilli, R.; La Regina, G.; Silvestri, R.; Mirabelli, C.; et al. (J. Med. Chem., 2018)

(untitled) - Karrouchi, K.; Radi, S.; Ramli, Y.; Taoufik, J.; Mabkhot, Y. N.; Al-aizari, F. A.; Ansar, M. (Molecules, 2018)

(untitled) - Nandi, G. C.; Singh, M. S.; Ila, H.; Junjappa, H. (Eur. J. Org. Chem., 2012)

(untitled) - Yoshikawa, Y.; Katsuta, H.; Kishi, J.; Yanase, Y. (J. Pestic. Sci. (Tokyo, Jpn.), 2011)

(untitled) - Numata, A.; Tanima, D.; Ando, M.; Iwawaki, Y. (Pyrazole derivatives and pesticides, 2013)

(untitled) - Wang, M.-M.; Huang, H.; Shu, L.; Liu, J.-M.; Zhang, J.-Q.; Yan, Y.-L.; Zhang, D.-Y. (Beilstein J. Org. Chem., 2020)

(untitled) - Wang, H.; Duffy, R. A.; Boykow, G. C.; Chackalamannil, S.; Madison, V. S. (J. Med. Chem., 2008)

(untitled) - Naoum, F.; Kasiotis, K. M.; Magiatis, P.; Haroutounian, S. A. (Molecules, 2007)

(untitled) - Slee, D. H.; Moorjani, M.; Zhang, X.; Lin, E.; Lanier, M. C.; Chen, Y.; Rueter, J. K.; Lechner, S. M.; Markison, S.; Malany, S.; Joswig, T.; Santos, M.; et al. (J. Med. Chem., 2008)

(untitled) - Lauria, A.; Abbate, I.; Patella, C.; Gambino, N.; Silvestri, A.; Barone, G.; Almerico, A. M. (Tetrahedron Lett., 2008)

(untitled) - Chandra, T.; Garg, N.; Lata, S.; Saxena, K. K.; Kumar, A. (Eur. J. Med. Chem., 2010)

(untitled) - Abdel-Hafez, E.-S. M. N.; Abuo-Rahma, G. E.-D. A. A.; Abdel-Aziz, M.; Radwan, M. F.; Farag, H. H. (Bioorg. Med. Chem., 2009)

(untitled) - Lv, P.-C.; Li, H.-Q.; Sun, J.; Zhou, Y.; Zhu, H.-L. (Bioorg. Med. Chem., 2010)

(untitled) - Balbi, A.; Anzaldi, M.; Macciò, C.; Aiello, C.; Mazzei, M.; Gangemi, R.; Castagnola, P.; Miele, M.; Rosano, C.; Viale, M. (Eur. J. Med. Chem., 2011)

(untitled) - Hura, N.; Naaz, A.; Prassanawar, S. S.; Guchhait S. K; Panda, D. (ACS Omega, 2018)

(untitled) - El-Sabbagh, O. I.; Baraka, M. M.; Ibrahim, S. M.; Pannecouque, C.; Andrei, G.; Snoeck, R.; Balzarini, J.; Rashad, A. A. (Eur. J. Med. Chem., 2009)

(untitled) - Hall, A.; Billinton, A.; Brown, S. H.; Clayton, N. M.; Chowdhury, A.; Giblin, G. M. P.; Goldsmith, P.; Hayhow, T. G.; Hurst, D. N.; Kilford, I. R.; Naylor, A.; Passingham, B.; et al. (Bioorg. Med. Chem. Lett., 2008)

(untitled) - Sharshira, E. M.; Hamada, N. M. M. (Molecules, 2012)

(untitled) - Chimenti, F.; Bolasco, A.; Manna, F.; Secci, D.; Chimenti, P.; Befani, O.; Turini, P.; Giovannini, V.; Mondovì, B.; Cirilli, R.; La Torre, F. (J. Med. Chem., 2004)

(untitled) - Partridge, F. A.; Forman, R.; Bataille, C. J. R.; Wynne, G. M.; Nick, M.; Russell, A. J.; Else, K. J.; Sattelle, D. B. (Beilstein J. Org. Chem., 2020)

(untitled) - Dale, D. J.; Dunn, P. J.; Golightly, C.; Hughes, M. L.; Levett, P. C.; Pearce, A. K.; Searle, P. M.; Ward, G.; Wood, A. S. (Org. Process Res. Dev., 2000)

(untitled) - Dunn, P. J.; Galvin, S.; Hettenbach, K. (Green Chem., 2004)

(untitled) - Ghozlan, S. A. S.; Badahdah, K. O.; Abdelhamid, I. A. (Beilstein J. Org. Chem., 2007)

(untitled) - Penning, T. D.; Talley, J. J.; Bertenshaw, S. R.; Carter, J. S.; Collins, P. W.; Docter, S.; Graneto, M. J.; Lee, L. F.; Malecha, J. W.; Miyashiro, J. M.; Rogers, R. S.; Rogier, D. J.; et al. (J. Med. Chem., 1997)

(untitled) - Baumann, M.; Baxendale, I. R.; Ley, S. V.; Nikbin, N. (Beilstein J. Org. Chem., 2011)

(untitled) - Kameyama, T.; Nabeshima, T. (Neuropharmacology, 1978)

US Patent - Chen, C.-M.; Kositprapa, U. (Pharmaceutical formulations containing a non-steroidal antiinflammatory drug and a proton pump inhibitor, 2005)

(untitled) - Kotagiri, V. K.; Suthrapu, S.; Reddy, J. M.; Rao, C. P.; Bollugoddu, V.; Bhattacharya, A.; Bandichhor, R. (Org. Process Res. Dev., 2007)

(untitled) - Wang, M.; Zhang, J.; Liu, J.; Xu, C.; Ju, H. (J. Lumin., 2002)

(untitled) - Burschka, J.; Kessler, F.; Nazeeruddin, M. K.; Grätzel, M. (Chem. Mater., 2013)

(untitled) - Chou, P.-T.; Chi, Y. (Chem. – Eur. J., 2007)

(untitled) - Molteni, G.; Buttero, P. D. (Tetrahedron: Asymmetry, 2005)

(untitled) - Tu, X.-J.; Hao, W.-J.; Ye, Q.; Wang, S.-S.; Jiang, B.; Li, G.; Tu, S.-J. (J. Org. Chem., 2014)

(untitled) - Yadav, P.; Awasthi, A.; Gokulnath, S.; Tiwari, D. K. (J. Org. Chem., 2021)

(untitled) - Castagnolo, D.; Schenone, S.; Botta, M. (Chem. Rev., 2011)

(untitled) - Bartlett, P. A.; Spear, K. L.; Jacobsen, N. E. (Biochemistry, 1982)

(untitled) - Yu, K.-L.; Torri, A. F.; Luo, G.; Cianci, C.; Grant-Young, K.; Danetz, S.; Tiley, L.; Krystal, M.; Meanwell, N. A. (Bioorg. Med. Chem. Lett., 2002)

(untitled) - Gannon, M. K.; Holt, J. J.; Bennett, S. M.; Wetzel, B. R.; Loo, T. W.; Bartlett, M. C.; Clarke, D. M.; Sawada, G. A.; Higgins, J. W.; Tombline, G.; Raub, T. J.; Detty, M. R. (J. Med. Chem., 2009)

(untitled) - Banala, S.; Süssmuth, R. D. (ChemBioChem, 2010)

(untitled) - Mahanta, N.; Szantai-Kis, D. M.; Petersson, E. J.; Mitchell, D. A. (ACS Chem. Biol., 2019)

(untitled) - Kumar, K.; Konar, D.; Goyal, S.; Gangar, M.; Chouhan, M.; Rawal, R. K.; Nair, V. A. (ChemistrySelect, 2016)

(untitled) - Chaubey, T. N.; Borpatra, P. J.; Sharma, A.; Pandey, S. K. (Org. Lett., 2022)

(untitled) - Jagodziński, T. S. (Chem. Rev., 2003)

(untitled) - Bach, A.; Eildal, J. N. N.; Stuhr-Hansen, N.; Deeskamp, R.; Gottschalk, M.; Pedersen, S. W.; Kristensen, A. S.; Strømgaard, K. (J. Med. Chem., 2011)

(untitled) - Nakamura, H.; Noh, J. Y.; Itoh, K.; Fukata, S.; Miyauchi, A.; Hamada, N. (J. Clin. Endocrinol. Metab., 2007)

(untitled) - Lincke, T.; Behnken, S.; Ishida, K.; Roth, M.; Hertweck, C. (Angew. Chem., 2010)

(untitled) - Hisano, T.; Yabuta, Y. (Chem. Pharm. Bull., 1973)

Strategies for Organic Drug Synthesis and Design - Lednicer, D. (John Wiley, 2008)

(untitled) - Montalbetti, C. A. G. N.; Falque, V. (Tetrahedron, 2005)

(untitled) - Dunetz, J. R.; Magano, J.; Weisenburger, G. A. (Org. Process Res. Dev., 2016)

(untitled) - Nandi, G. C.; Samai, S.; Singh, M. S. (J. Org. Chem., 2010)

(untitled) - Lau, W. C.; Waskell, L. A.; Watkins, P. B.; Neer, C. J.; Horowitz, K.; Hopp, A. S.; Tait, A. R.; Carville, D. G. M.; Guyer, K. E.; Bates, E. R. (Circulation, 2003)

(untitled) - Abraham, I.; MacDonald, K.; Hermans, C.; Aerts, A.; Lee, C.; Brie, H.; Vancayzeele, S. (Vasc. Health Risk Manage., 2011)

(untitled) - Okamoto, K.; Yamamoto, T.; Kanbara, T. (Synlett, 2007)

(untitled) - Pathare, S. P.; Chaudhari, P. S.; Akamanchi, K. G. (Appl. Catal., A, 2012)

(untitled) - Curphey, T. J. (J. Org. Chem., 2002)

(untitled) - Pathak, U.; Pandey, L. K.; Mathur, S.; Suryanarayana, M. V. S. (Chem. Commun., 2009)

(untitled) - Manaka, A.; Sato, M. (Synth. Commun., 2005)

(untitled) - Xu, H.; Deng, H.; Li, Z.; Xiang, H.; Zhou, X. (Eur. J. Org. Chem., 2013)

(untitled) - Yin, Z.; Zheng, B. (J. Sulfur Chem., 2013)

(untitled) - Wei, J.; Li, Y.; Jiang, X. (Org. Lett., 2016)

(untitled) - Tayade, Y. A.; Jangale, A. D.; Dalal, D. S. (ChemistrySelect, 2018)

(untitled) - Sharma, S.; Malakar, C. C.; Singh, V. (Asian J. Org. Chem., 2020)

(untitled) - Singh, M.; Vaishali; Kumar, R.; Singh, V. (ChemistrySelect, 2020)

(untitled) - Nguyen, T. B. (Adv. Synth. Catal., 2017)

(untitled) - Nguyen, T. B. (Adv. Synth. Catal., 2020)

(untitled) - Singh, M.; Awasthi, P.; Singh, V. (Eur. J. Org. Chem., 2020)

(untitled) - Wu, K.; Ling, Y.; Ding, A.; Jin, L.; Sun, N.; Hu, B.; Shen, Z.; Hu, X. (Beilstein J. Org. Chem., 2021)

(untitled) - Ilkin, V.; Berseneva, V.; Beryozkina, T.; Glukhareva, T.; Dianova, L.; Dehaen, W.; Seliverstova, E.; Bakulev, V. (Beilstein J. Org. Chem., 2020)

(untitled) - Tang, Q.; Yin, X.; Kuchukulla, R. R.; Zeng, Q. (Chem. Rec., 2021)

(untitled) - Liu, S.; Deng, G.-J.; Huang, H. (Synlett, 2021)

(untitled) - Beletskaya, I. P.; Ananikov, V. P. (Chem. Rev., 2022)

(untitled) - Yu, Z.; Su, J.; Huang, C.; Wei, J.; Han, D. L.; Ye, D. Q.; Li, Y. (Asian J. Org. Chem., 2022)

(untitled) - Koyanagi, A.; Murata, Y.; Hayakawa, S.; Matsumura, M.; Yasuike, S. (Beilstein J. Org. Chem., 2022)

(untitled) - Pošta, M.; Zima, V.; Poštová Slavětínská, L.; Matoušová, M.; Beier, P. (Beilstein J. Org. Chem., 2022)

(untitled) - Pathania, S.; Narang, R. K.; Rawal, R. K. (Eur. J. Med. Chem., 2019)

(untitled) - Sharma, S.; Paul, A. K.; Singh, V. (New J. Chem., 2020)

(untitled) - Devi, N.; Singh, D.; Sunkaria, R. K.; Malakar, C. C.; Mehra, S.; Rawal, R. K.; Singh, V. (ChemistrySelect, 2016)

(untitled) - Devi, N.; Shankar, R.; Singh, V. (J. Heterocycl. Chem., 2018)

(untitled) - Nag, S.; Singh, V.; Batra, S. (ARKIVOC, 2007)

(untitled) - Mondal, R.; Mallik, A. K. (Org. Prep. Proced. Int., 2014)

(untitled) - Dheer, D.; Rawal, R. K.; Singh, V.; Sangwan, P. L.; Das, P.; Shankar, R. (Tetrahedron, 2017)

(untitled) - Sankari Devi, E.; Alanthadka, A.; Tamilselvi, A.; Nagarajan, S.; Sridharan, V.; Maheswari, C. U. (Org. Biomol. Chem., 2016)